1989
DOI: 10.1088/0031-9155/34/2/002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the elastic behaviour of central venous PVC, polyurethane and silicone catheters

Abstract: Eighty used and 20 new silicone, polyurethane and polyvinylchloride central venous catheters were tested to establish the Young's modulus and the bending stiffness of the catheters and their introducers. The catheters were subjected to longitudinal traction forces and their lengthening measured. Young's modulus and the geometric moment of inertia were then calculated. It is shown that polyurethane catheters show least variation in their elastic characteristics, and that silicone catheters offer least resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…Only a single‐lumen tunneled catheter (Hickman) was used for ELT because several studies have reported that ethanol can erode catheters made with materials other than polyurethane 13 . ‐ 15 Before the initiation of a new HPN cycle, the lumen was flushed using normal saline similar to previous studies 12 …”
Section: Methodsmentioning
confidence: 99%
“…Only a single‐lumen tunneled catheter (Hickman) was used for ELT because several studies have reported that ethanol can erode catheters made with materials other than polyurethane 13 . ‐ 15 Before the initiation of a new HPN cycle, the lumen was flushed using normal saline similar to previous studies 12 …”
Section: Methodsmentioning
confidence: 99%
“…This particular catheter shows more ductility than we think is desirable. Polyurethane catheters used in the central venous system have been shown to have less variation in their elastic characteristics than those made of Polyvinyl or silicone, with silicone catheters offering less resistance to bending (Cervera et al, 1989). It is apparent that the optimum balance between ductility and stiffness remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…We model the catheter using 6871 tetrahedra defined by 3185 nodes and set its Young's modulus to 8700 KPa for silicon. 24 The arteries, which can range in diameter from 2.5 mm to 6 mm are modeled using 8330 nodes that define 5548 tetrahedra forming a single layer over the outside . .................................................................... …”
Section: Synchronized Fish Swimmingmentioning
confidence: 99%